2010
DOI: 10.1007/s00464-009-0871-y
|View full text |Cite
|
Sign up to set email alerts
|

Advantages of fast-track recovery after laparoscopic right hemicolectomy for colon cancer

Abstract: Fast-track recovery is independently associated with a shorter LOS and decreased morbidity after laparoscopic right hemicolectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
30
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 12 publications
1
30
0
1
Order By: Relevance
“…The readmission rates were within the wide range reported in the literature (2·9-27 per cent) 3,12,18,22 . Although not significant, this may have been a type II error.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…The readmission rates were within the wide range reported in the literature (2·9-27 per cent) 3,12,18,22 . Although not significant, this may have been a type II error.…”
Section: Discussionmentioning
confidence: 54%
“…Recently, fast-track approaches have been used in laparoscopic procedures, with a reported median hospital stay of 3 days 19 and 4 days 22 . The present results showed that further benefits can be achieved with ERP beyond the previous minimally invasive FTP within the same practice 18,19 .…”
Section: Discussionmentioning
confidence: 77%
“…Since the introduction of laparoscopic colorectal resections and ERAS, various groups have investigated the optimum combination of operative technique and peri-operative management [17,18,[26][27][28][29][30]. Studies have demonstrated laparoscopic colorectal resections together with ERAS reduces hospital stay by 2 -4 days compared to open procedures with ERAS [4,16].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated laparoscopic colorectal resections together with ERAS reduces hospital stay by 2 -4 days compared to open procedures with ERAS [4,16]. When comparing laparoscopic procedures within an ERAS setting or traditional post-operative management, the former combination has shown to be beneficial in terms of length of stay and wound infections [28].…”
Section: Discussionmentioning
confidence: 99%
“…To assess the effectiveness of laparoscopic colectomy in reducing the hospital stay and postoperative morbidity, Tsikitis et al [3] compared the results for patients who recover on a fast-track (FT) protocol after laparoscopic colectomy with those for patients who recover on a standard (non-FT) protocol. The authors analyzed the data for a cohort of 197 consecutive patients with colon cancer who underwent laparoscopically assisted right hemicolectomy.…”
mentioning
confidence: 99%